Pengaruh Corporate Social Responsibility, Leverage, dan Kebijakan Dividen terhadap Nilai Perusahaan - Nur Azizah Basmar; Muhammad Azhim Dzaky Ghaniyyul Akbar (Tangible Journal, 2026)
This study aims to analyze the influence of Corporate Social Responsibility (CSR), Leverage, and Dividend Policy on the value of mining companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. The approach used is a quantitative approach with secondary data obtained from the company's financial statements through the official website of www.idx.co.id. The sampling technique used the purposive sampling method with certain criteria, until 13 companies were obtained as a sample with a total of 29 observation data. Company value is measured using Price Book Value (PBV), CSR is measured using the Corporate Social Responsibility Index (CSRI), Leverage is used the Debt to Equity Ratio (DER), and dividend policy is used the Dividend Payout Ratio (DPR). The results of the study show that CSR has a negative and significant effect on the company's value. Meanwhile, Leverage has a positive and significant effect on the value of the company. Meanwhile, the Dividend Policy has no effect and is not significant on the value of mining companies listed on the IDX during the research period.